Does Auditor Independence Mediate the Relationship Between Auditor Rotation and Audit Quality? - Lutfi Ardhani; Bambang Subroto; Bambang Hariadi (Universitas Negeri Malang, 2019)
This research was conducted based on issues related to the decline in public trust in the ability of auditors to produce quality audits. This study aims to provide empirical evidence about audit quality that is influenced by auditor rotation. This research aims at providing an empirical evidence of the influence of auditor rotation on audit quality. This is an explanatory study using 90 auditors in Indonesia as its sample. The sample is taken using random sampling and the data are collected using questionnaire and interview with several auditors. The research results indicate that auditor rotation is not found to have direct influence on audit quality. The research also fails to provide empirical evidences of the role of auditor’s independence auditor as an intervening variable. Nevertheless, the research does proves that auditor’s independence has positive influence on audit quality.